Mathematics - Miller, Jim.; Newman,Graham; Procter, Maralyn (Thomas Nelson Limited : Thomas Nelson, 1994)
A comprehensive secondary maths course designed and written specifically for the National Curriculum. There are worked examples and numerous graded exercises. This students' book provides support for students having difficulty with the maths covered in the "x" series.
Keywords: Mathematics -- Study and teaching (Secondary).